Three years' interventional neurology experience in Turkey with the Thrombite thrombectomy device in large vessel occlusion in the anterior circulation: safety, efficacy, and clinical outcome - Akpinar, Cetin Kursad; Gurkas, Erdem; Ozdemir, Atilla Ozcan; Dogan, Hasan; Onalan, Aysenur; Yildirim, Serhan; Topaktas, Berkhan (Frontiers Media Sa, 2024)
Introduction While the Thrombite device differs from the Solitare stent with its Helical open-side structure feature, it shows great similarity with its other features. We assessed the Thrombite device's effectiveness and safety in this study.Materials and methods The study was a retrospective analysis of patients who were included in the Turkish Interventional Neurology database and who had mechanical thrombectomy with the Thrombite device as the first choice between January 2020 and January 2023. The type of study is descriptive research.Result Using the Thrombite thrombectomy device, 525 patients received treatment. The median baseline National Institutes of Health Stroke Scale (NIHSS) score was 13, the median initial Alberta Stroke Program Early Computed Tomography (ASPECT) score was 8, and the mean patient age was 68.6+11.7 years. Between the groin puncture and the successful recanalization, the median time was 34 minutes (interquartile range [IQR]: 15-45). 48.2% (modified treatment in cerebral infarction; mTICI) 2b/3% and 33.9% (mTICI 2c/3) were the first-pass recanalization rates. In the end, 87.7% of patients had effective recanalization (thrombolysis in cerebral infarction 2b/3). In the first-pass subgroup, the favorable functional result (modified Rankin Scale 0-2) was 51.8%, while it was 41.6% for the entire patient population. The rate of embolization into new territory/different territory were 2.1/0.1%. 23 patients (4.5%) had symptomatic hemorrhage.Conclusion The Thrombite device showed a good safety profile and high overall successful recanalization rates in our experience.
Keywords: acute stroke; mechanical thrombectomy; thrombectomy device; first pass complete reperfusion; technique